Q:

use foil (a + 3)(a - 2)

Accepted Solution

A:
Answer: [tex]\left(a+3\right)\left(a-2\right)=a^2+a-6=[/tex]Step-by-step explanation:Given expression is [tex]\left(a+3\right)\left(a-2\right)[/tex]. Now we need to multiply this using FOIL.F = First [tex]=\left(a\right)\left(a\right)= a^2[/tex]O = Outside [tex]=\left(a\right)\left(-2\right)= -2a[/tex]I = Inside [tex]=\left(3\right)\left(a\right)= 3a[/tex]L = Last [tex]=\left(3\right)\left(-2\right)= -6[/tex]Hence we get : [tex]\left(a+3\right)\left(a-2\right)=a^2-2a+3a-6=a^2+a-6=[/tex]